2017
DOI: 10.17265/2161-6256/2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Climatology of Guinea: Study of Climate Variability in N’zerekore

Abstract: N'zerekore is a geographical region of Guinea, which houses a weather observatory located at longitude 8.8°, latitude 7.7° and altitude 475 m. This region is of major socio-economic interest for the country. The climatological study of this region shows the variability of each parameter. The objective of this study was to analyze meteorological parameters trends and to assess the space-time evolution of some agro-climatic risks related to the main trends observed in the meteorological parameters regime of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…Zerekore was historically humid, but it has been warming up over the years. This could be related to climate change with links to deforestation (Loua et al 2017).…”
Section: -Results and Discussionmentioning
confidence: 99%
“…Zerekore was historically humid, but it has been warming up over the years. This could be related to climate change with links to deforestation (Loua et al 2017).…”
Section: -Results and Discussionmentioning
confidence: 99%
“…This pejoration of the rainfall regime was particularly severe during the beginning (June) and the end (September and October) of the crops growth season. Analysing N’Zérekoré rainfall data for the 1931–2014, Loua et al ( 2017 ) reported that the higher variability of the annual rainfall during the period 1994–2014 was associated with a shorter duration of the rainy season (later beginning and earlier ending) and a less predictable date for the establishment of the rainy season.…”
Section: Discussionmentioning
confidence: 99%